2020
DOI: 10.3390/jcm9030720
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Control of Human Locomotion as a New Determinant of Age-Related Sarcopenia: An Exploratory Study

Abstract: Sarcopenia is a muscle disease listed within the ICD-10 classification. Several operational definitions have been created for sarcopenia screening; however, an international consensus is lacking. The Centers for Disease Control and Prevention have recently recognized that sarcopenia detection requires improved diagnosis and screening measures. Mounting evidence hints towards changes in the corticospinal communication system where corticomuscular coherence (CMC) reflects an effective mechanism of corticospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…It is characterized by quantitative and qualitative alterations in muscles that may emerge from middle age onwards [3] and cumulatively occur in people with chronic diseases and an inactive lifestyle [4]. The prevalence of sarcopenia in Europe was between 11 and 20% in healthy men and women aged ≥60 years in 2016 [5,6] and an accumulated 17% in a recently studied Swiss sample in the Italian speaking part of Switzerland where seven different Sarcopenia definitions were applied [7]. The prevalence significantly increases with age and is expected to rise within the next 30 years, particularly in the highest age groups [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by quantitative and qualitative alterations in muscles that may emerge from middle age onwards [3] and cumulatively occur in people with chronic diseases and an inactive lifestyle [4]. The prevalence of sarcopenia in Europe was between 11 and 20% in healthy men and women aged ≥60 years in 2016 [5,6] and an accumulated 17% in a recently studied Swiss sample in the Italian speaking part of Switzerland where seven different Sarcopenia definitions were applied [7]. The prevalence significantly increases with age and is expected to rise within the next 30 years, particularly in the highest age groups [5].…”
Section: Introductionmentioning
confidence: 99%
“…This rapid loss of muscle strength is explained by mitochondrial damage and protein degradation [ 52 54 ] typical for CKD patients. However, changes in grip strength are largely reflective of decreased integrity of the nervous system [ 55 ] and sarcopenia is also linked to changes in the central nervous system [ 56 , 57 ]. This would hint to the possibility of gait disorders in CKD caused by peripheral and central factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on corticospinal activity have been performed in PD patients and healthy controls during gait. One study found corticospinal control of human locomotion as a new determinant of age-related sarcopenia through comparison of corticomuscular coherence (CMC) between sarcopenic and non-sarcopenic older adults during gait, which may hint at a novel possible mechanism derived from corticospinal control of locomotion in age-related sarcopenia ( 36 ). Another study found that older healthy controls and PD participants had significantly decreased CMC and electromyography (EMG) power at low beta frequencies (13–21 Hz) compared with young healthy controls, whereas there was no difference between the older healthy and PD groups ( 37 ).…”
Section: Discussionmentioning
confidence: 99%